Analysis And Design Of A Survey Application To Measure Outpatient Loyalty Using The Customer Relationship Management Method - Albert, Albert; Halawa, Misdayanti; Manik, Rifqa Yolandha Efreymind; Harmaja, Okta Jaya (Jurnal Sistem Informasi dan Ilmu Komputer, 2024)
Addressing patient complaints regarding the services provided indicates potential issues with service quality, possibly even non-compliance with procedures. To identify such issues, regular surveys must be conducted. Conducting surveys requires specialized human resources and significant costs, which can be burdensome for hospitals. Therefore, a software application was developed to conduct surveys and process the data, allowing results to be analyzed and used for policy-making. This software uses the Customer Relationship Management (CRM) method. The software was tested for 6 months at RSU Royal Prima. In the first month, many service quality issues were identified, and SOPs were not followed correctly. However, in the following months, these issues were addressed, and after 6 months of testing, the survey software proved to be beneficial with relatively low costs, as it did not require specialized human resources. In other words, the CRM survey software can enhance transparency, responsiveness, and service quality, as well as manage patient satisfaction levels without relying on third parties.